2015
DOI: 10.1007/s13277-015-3805-4
|View full text |Cite
|
Sign up to set email alerts
|

The elevated preoperative derived neutrophil-to-lymphocyte ratio predicts poor clinical outcome in breast cancer patients

Abstract: Existing preclinical and clinical data suggest that the presence of a systemic inflammatory response plays a critical role in the progression of several solid tumors. The derived neutrophil-to-lymphocyte ratio (dNLR) represents an easily determinable marker of systemic inflammation and has been proposed as a potential prognostic marker. The present study was performed to validate and further clarify the prognostic relevance of an elevated pre-treatment dNLR in a large cohort of European breast cancer patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 48 publications
3
39
0
1
Order By: Relevance
“…This finding is consistent with other smaller studies demonstrating that elevated NLR portends poor prognosis in solid tumor malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Other studies in patients with hepato-pancreato-biliary (HPB) cancers agree with the findings presented in this paper. In a study of 452 patients who underwent a HPB procedure for malignant disease, NLR >5 was found to be associated with worse OS.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with other smaller studies demonstrating that elevated NLR portends poor prognosis in solid tumor malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Other studies in patients with hepato-pancreato-biliary (HPB) cancers agree with the findings presented in this paper. In a study of 452 patients who underwent a HPB procedure for malignant disease, NLR >5 was found to be associated with worse OS.…”
Section: Discussionsupporting
confidence: 91%
“…Our study also found that mALNR was most significantly related to prognosis including recurrence and mortality. The metastatic lymph node ratio in other various cancer types is also thought to be an independent prognostic factor [212223]. Similar to previous studies, we found that a higher mALNR was associated with poor long-term prognosis in breast cancer.…”
Section: Discussionsupporting
confidence: 89%
“…A low PNI has been found to be associated with a poor prognosis in various malignancies . Moreover, other inflammation based scores such as derived neutrophil‐to‐lymphocyte ratio (dNLR) and lymphocyte‐to‐monocyte ratio (LMR) were also confirmed to be valuable in predicting tumor outcomes …”
Section: Introductionmentioning
confidence: 95%
“…23,24 Moreover, other inflammation based scores such as derived neutrophil-to-lymphocyte ratio (dNLR) and lymphocyte-to-monocyte ratio (LMR) were also confirmed to be valuable in predicting tumor outcomes. 25,26 However, to our knowledge, dNLR, LMR, PNI, and plasma fibrinogen have never been investigated in patients with MTC. Furthermore, which inflammation based scores are more suitable for predicting clinical outcomes, including lymph node metastasis, capsule invasion, advanced tumor stages, and recurrence, remain unclear in MTC.…”
mentioning
confidence: 99%